Emergence and dissemination of a linezolid-resistant Staphylococcus capitis clone in Europe. (19th December 2016) - Butin, M.; Martins-Simões, P.; Pichon, B.; Leyssene, D.; Bordes-Couecou, S.; Meugnier, H.; Rouard, C.; Lemaitre, N.; Schramm, F.; Kearns, A.; Spiliopoulou, I.; Hyyryläinen, H.-L.; et al.
Abstract : Objectives: We investigated the epidemiological, clinical, microbiological and genetic characteristics of linezolid-resistant (LZR) Staphylococcus capitis isolates from French ICUs, and compared them with LZR S. capitis isolates from other European countries. Methods: All LZR isolates were subjected to antimicrobial susceptibility testing (AST) and the presence of cfr and optrA genes as well as mutations in the 23S rRNA and ribosomal proteins were investigated using specific PCR with sequencing. The genetic relationship between isolates was investigated using PFGE and WGS. Epidemiological data concerning LZR S. capitis were collected retrospectively in French microbiology laboratories. Results: Twenty-one LZR isolates were studied: 9 from France, 11 from Greece and 1 from Finland. All were resistant to methicillin and aminoglycosides. In addition, this unusual AST profile was identified in S. capitis isolates from seven French hospitals, and represented up to 12% of the S. capitis isolates in one centre. A G2576T mutation in 23S rRNA was identified in all isolates; cfr and optrA genes were absent. All isolates belonged to the same clone on the basis of their PFGE profiles, whatever their geographical origin. WGS found at most 212 SNPs between core genomes of the LZR isolates. Conclusions: We identified and characterized an LZR S. capitis clone disseminated in three European countries, harbouring the same multiple resistance and a G2576T mutation in the 23S rRNA. The possible unrecognized wider distribution of this clone, belonging to a species classically regarded as a low-virulence skin colonizer, is of major concern not least because of the increasing use of oxazolidinones.